INTERRUPTION OF GESTATION IN A BITCH USING A COMBINED TREATMENT OF CLOPROSTENOL AND CABERGOLINE - Sánchez R., Alfonso (2010)
The effectiveness of a combined treatment of cloprostenol and cabergoline was evaluated for interruption of gestation in bitches. A clinical experience is reported in an English bulldog bitch with a gestation of 30 days. The treatment was administrated every 24 hours and consisted in 5 μg/kg of cabergoline, orally, followed 30 minutes later by 1 μg/kg of cloprostenol, via subcutaneous. Physiological constants, effects post administration, and ecographic evolution of the gestation was evaluated. Also, progesterone concentration was determined in two blood samples using a quantitative commercial kit. Changes in gestational vesicles were observed at day 3 of treatment, and a lower cardiac frequency (<180 bpm) were recorded on day 4. A fetal expulsion occurred few hours later. Ultrasound on day 5 showed absence of vesicles and fetuses. Serum progesterone concentration on day 3 was 1 to 2.5 ng/ml, incompatible with the maintenance of gestation, and on day 5 was <1 ng/ml. The results allowed confirming the effectiveness of this protocol to interrupt gestations in bitches, highlighting the short duration of the treatment (4 days).